Effect of online problem-solving counseling on the sexual anxiety and intimacy of women with recurrent pregnancy loss: A clinical trial - Shahla Mohammadkhani; Nasrin Ghasemi; Tayebeh Mokhtari Sorkhani; Mahshid Bokaie (Shahid Sadoughi University of Medical Sciences, 2024)
Abstract Background: Recurrent pregnancy loss (RPL) creates complex reproductive conditions among women. Problem-solving therapy is one of the sexual health approaches. Objective: This study was designed to investigate the effect of online problem-solving counseling on the sexual anxiety and intimacy of women with RPL. Materials and Methods: A randomized clinical trial was conducted at Abortion Research Center in Yazd, Iran between March and August 2023. A total of 70 women with RPL were assigned into 2 groups, that is, intervention and control using random allocation software (n = 35/each). The intervention group received 8 sessions of sexual counseling on problem solving. The control group received an educational pamphlet. The primary outcome was sexual anxiety, and the secondary outcome was sexual intimacy. The data were collected using questionnaires based on sexual anxiety and intimacy. The questionnaires were completed before, after, and 1 month after the study. Results: A total of 70 participants were included in the final analysis. The mean score of sexual anxiety in the 8 th and 12 th wk was significantly less in the online group than in control group (p < 0.001). The mean score of sexual intimacy in the 8 th and 12 th wk was significantly higher in the online group than in control group (p < 0.001). Conclusion: Problem-solving-based sexual health counseling programs may improve sexual anxiety and intimacy in women with RPL. It is recommended to use a sexual health counseling method in RPL centers when considering the effectiveness of this type of training.